The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21051773
|View full text |Cite
|
Sign up to set email alerts
|

Obatoclax, a Pan-BCL-2 Inhibitor, Downregulates Survivin to Induce Apoptosis in Human Colorectal Carcinoma Cells Via Suppressing WNT/β-catenin Signaling

Abstract: Colorectal cancer (CRC) is a highly prevailing cancer and the fourth leading cause of cancer mortality worldwide. Aberrant expression of antiapoptotic BCL-2 family proteins is closely linked to neoplastic progression and chemoresistance. Obatoclax is a clinically developed drug, which binds antiapoptotic BCL-2, BCL-xL, and MCL-1 for inhibition to elicit apoptosis. Survivin is an antiapoptotic protein, whose upregulation correlates with pathogenesis, therapeutic resistance, and poor prognosis in CRC. Herein, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Therefore, the high hypoxia pattern could limit the efficacy of sorafenib, further giving rise to the poor sensitivity of C2 [ 36 ]. Moreover, C2 exhibited more sensitivity to obatoclax, which might be due to obatoclax promoted tumor cells apoptosis by antagonizing WNT/ β -catenin signaling that significantly was enriched in C2 [ 54 ]. In addition, we developed a risk signature termed HARS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the high hypoxia pattern could limit the efficacy of sorafenib, further giving rise to the poor sensitivity of C2 [ 36 ]. Moreover, C2 exhibited more sensitivity to obatoclax, which might be due to obatoclax promoted tumor cells apoptosis by antagonizing WNT/ β -catenin signaling that significantly was enriched in C2 [ 54 ]. In addition, we developed a risk signature termed HARS.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 family members have been shown to play a pivotal role in regulating cell death by acting as critical decision points in the apoptosis pathway. 50 A previous study showed that the overexpression of Bcl-2 suppressed apoptosis following SCI. 24 This finding is in accordance with our results, which showed the upregulation of Bcl-2 after miR-135a-5p transfection ( Figure 3 G).…”
Section: Discussionmentioning
confidence: 99%
“…The luciferase reporter vector for β-catenin-mediated, TCF/LEF-mediated, transcriptional activity M50 Super 8x TOPFlash (Addgene plasmid #12456) and the TOPFlash mutant vector M51 Super 8x FOPFlash (Addgene plasmid #12457) were gifts from Professor Randall Moon. The pBabe-HA–∆N90-β-catenin plasmid, a pBabe-based vector for the ectopic expression of an N-terminal, hemagglutinin (HA) epitope-tagged, dominant–active β-catenin mutant, has been described in detail in our previous report [ 34 ]. Production of pBabe-derived retroviral particles and subsequent infection to target cells was performed according our established protocols [ 35 ].…”
Section: Methodsmentioning
confidence: 99%